Steven Spielberg Presents Taken - Eisner, Breck, 1970-; Dakota, Fanning; Matt Frewer; Heather Donahue; Emily Bergl; Adam Kaufman (Sci-Fi Channel, The Vancouver British Columbia Canada, 2002)
Taken spans five decades and four generations, and centers on three families: the Keys, the Crawfords, and the Clarkes. Nightmares of abduction by extraterrestrials during World War II haunt Russell Keys; the Roswell incident transforms Owen Crawford from ambitious Air Force captain to amoral shadow government conspirator; and an alien visitor impregnates an unhappily-married Sally Clarke. As the decades go by, the heirs of each are affected by the machinations of the aliens, culminating with the birth of Allie Keys, the final product of the aliens' experimentation and the key to their future.
Language(s): English Subtitle(s): English
Keywords: Television; Science Fiction and Fantasy